TP5.2.14 A quality improvement project: Engaging and educating our thyroidectomy patients. (28th October 2021) - Aderombi, Adetayo; Mahfouz, Yasmin; Wu, Fiona; Beatson, Kevin; Ahmed, Ibrahim
Abstract: Aims: Hypocalcaemia can occur in up to 30% of patients post-total thyroidectomy. Severe hypocalcaemia can lead to life-threatening tetany and seizures. As part of the consent process, risks are discussed typically face-to-face, often with the aid of anatomy illustrations. As tele-consultations become increasingly commonplace, patient-information leaflets (PILs) can be invaluable in enhancing informed consent, and empowering patients regarding their own care. We performed a quality improvement project to assess the feasibility and effects of distributing PILs following consultations to improve patients' understanding of post-operative complications (specifically hypocalcaemia). Methods: A retrospective review of post-total thyroidectomy patients was performed from January 2019 to January 2020. A telephone survey was conducted to assess each patient's understanding of post-operative complications. As tele-consultations began to be utilised during the COVID-19 pandemic, we designed a simple PIL to distribute to patients awaiting elective total thyroidectomy aiming to improve health literacy. Following distribution of PILs, the survey was repeated to evaluate feasibility and effectiveness. Results: Conclusions: A simple and inexpensive intervention, PILs can be distributed to patients awaiting elective surgery to improve health literacy, and reduce potential patient harm.